2014
DOI: 10.1136/jech-2014-203935
|View full text |Cite
|
Sign up to set email alerts
|

Spatial, temporal and relational patterns in respondent-driven sampling: evidence from a social network study of rural drug users

Abstract: Background Respondent-driven sampling (RDS) has become a common tool for recruiting high-risk populations for HIV research. However, few studies have explored the influence of geospatial proximity and relationship-level characteristics on RDS recruitment, particularly among high-risk individuals residing in rural areas of the US. Methods In a social network study of 503 drug users in rural Central Appalachia, interviewer-administered questionnaires were used to collect relationship-level data (eg, duration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 36 publications
0
46
0
2
Order By: Relevance
“…A separate study used dyadic analyses to compare RDS recruitment dyads with non-recruitment network dyads; the authors examined non-random recruitment based on drug use similarity, geographic proximity, demographic similarity and relationship-level characteristics (e.g., duration of relationship, frequency of communication, kinship, social/financial support, trust, drug use, and sex) and reported that RDS participants were significantly more likely to recruit kin and those with whom they had more frequent communication[33]. In this analysis, we used network simulations to assess outcome-correlated recruitment and geographic-correlated recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…A separate study used dyadic analyses to compare RDS recruitment dyads with non-recruitment network dyads; the authors examined non-random recruitment based on drug use similarity, geographic proximity, demographic similarity and relationship-level characteristics (e.g., duration of relationship, frequency of communication, kinship, social/financial support, trust, drug use, and sex) and reported that RDS participants were significantly more likely to recruit kin and those with whom they had more frequent communication[33]. In this analysis, we used network simulations to assess outcome-correlated recruitment and geographic-correlated recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited using respondent-driven sampling (RDS), in which participants were given three coupons to recruit their network members, who if enrolled in the study, were given three coupons to distribute, and so on; this process was initiated by 108 seeds (57 of whom recruited no one) and proceeded through a maximum of 14 waves (details described elsewhere [45, 46]). Once enrolled, participants completed questionnaires administered by community-based interviewers who had received training in human subjects’ research ethics.…”
Section: Methodsmentioning
confidence: 99%
“…A greater sense of community in rural Appalachia and differences in the composition of rural and urban drug use networks may also partially explain this finding. For example, compared with similarly recruited PWUD in urban settings, drug use networks in the larger PWUD cohort study in rural Appalachia were comprised of more family members; 15 the close interpersonal bonds that characterize Appalachian families 18 may partially explain the greater priority that rural participants placed on protecting the locations of others' homes.…”
Section: Discussionmentioning
confidence: 99%
“…7 Briefly, fifteen Mid-Atlantic city residents who reported drug use (past 6 months) were enrolled between November 2014 and April 2015. Between November 2015 and March 2016, twenty persons who reported drug use (past 6 months) were purposively selected for diversity on age, gender, arrest history, injection status, and type(s) of drug(s) used from an ongoing longitudinal study of PWUD in rural Eastern Kentucky (i.e., ‘SNAP’, described elsewhere 15 ). All study procedures and materials were reviewed and approved by Institutional Review Boards at [Blinded Institutions].…”
Section: Methodsmentioning
confidence: 99%